Proibicionismo como "Situação-Limite": diferentes abordagens sobre drogadição no ensino de ciências e biologia - Santos, Pablo Rabello de Oliveira (Universidade Federal de São Carlos, 2022)
This study was developed from the author's concerns regarding how drug addiction is treated in science and biology teaching. The treatment of drugs in the teaching of science and biology is the result of a complex historical process, resulting in a biological approach to the theme in schools. The biomedical conception of drug addiction uses classifications on different types of drugs, according to their effects on the body (disturbing, depressant and stimulant), as well as characterizes the dependent case based on the frequency, signs and symptoms of use. Dependence is treated as the ultimate end for drug use and the understanding of health is fragmented, reflecting on the biomedical conception adopted in schools, especially in biology and science classes. This conception, however, which should seal (and does seal) the prohibition of some substances and the legality of others, is full of arbitrariness. When we look closely at the Brazilian drug legislation and its consequences for your people, there is a disproportionality and a very clear cut of a portion of the population, who are the ones that in practice suffer from prohibitionist echoes, especially the population racialized as black, in which, the latest legislative movements show ethical setbacks. The story about prohibitionism screams out the reasons why we observe the current conjuncture. The questions proposed in this work were as follows: what are the different conceptions on this subject in science and biology teaching? What factors influence them? In this way, a broader understanding of the subject was aimed at, mainly in relation to the biomedical perspective and the bases of prohibitionism. Subsequently, the study will focus on teaching conceptions. The work is a theoretical work, making use of bibliographic research. Three main teaching concepts were found: biomedical, traditional (war on drugs) and damage reduction. The first one, using a biologizing character, the second, the fear on the subject, both aimed at abstinence from drug use. Finally, the last one brings important divergences with the others and within what is treated as “damage reduction” in a homogeneous way. We align ourselves with the broader harm reduction concept, which dialogues with a socioecological approach to health areas. Finally, it is understood in this work, using Paulo Freire, that in order to achieve a damage reduction perspective that aims the freedom and autonomy of the students, prohibitionism must be treated as a "limit situation", that is, a situation of social contradiction that prevents humanization and the glimpse of the “viable unprecedented”
Prohibitionism as a "Limit Situation": different approaches on drug uses in science and biology teaching
Keywords: Drogadição; Concepções de ensino sobre drogas; Proibicionismo; Drug addiction; Teaching conceptions about drugs; Prohibitionism; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM